2008
DOI: 10.1007/s00464-008-9930-z
|View full text |Cite
|
Sign up to set email alerts
|

Peroral transgastric endoscopic procedures in pigs: feasibility, survival, questionings, and pitfalls

Abstract: This study reports the feasibility of natural orifice transluminal endoscopic surgery (NOTES) procedures in a porcine survival model and impresses the efficacy, the safety, the complications, and some technical difficulties of transgastric NOTES procedures, which merit further evaluation in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…It is important to emphasise that all human studies need to be conducted with local independent review board (IRB) approval [28] to avoid unnecessary trials and some of the scepticism seen during the introduction of laparoscopic surgery. Although the published data on humans to date have shown favorable results, animal studies have shown serious intraoperative difficulties with the use of current technologies as well as postoperative complications of gastric closure such as peritonitis [29]. This also is highlighted by the operative difficulties and complications of transumbilical flexible endoscopic cholecystectomy reported by Palanivelu et al [27].…”
Section: Discussionmentioning
confidence: 97%
“…It is important to emphasise that all human studies need to be conducted with local independent review board (IRB) approval [28] to avoid unnecessary trials and some of the scepticism seen during the introduction of laparoscopic surgery. Although the published data on humans to date have shown favorable results, animal studies have shown serious intraoperative difficulties with the use of current technologies as well as postoperative complications of gastric closure such as peritonitis [29]. This also is highlighted by the operative difficulties and complications of transumbilical flexible endoscopic cholecystectomy reported by Palanivelu et al [27].…”
Section: Discussionmentioning
confidence: 97%
“…The ability to completely explore the abdomen has been confirmed in many animal investigations [1,35]. To date, however, there are few reports of a translumenal diagnostic exploration in a human model.…”
Section: Diagnostic Accuracymentioning
confidence: 93%
“…Blind access to the stomach was first described almost 30 years ago with Gauderer's account of the percutaneous endoscopic gastrostomy (PEG) tube [31]. To date, this approach has been reported in many different operations, including hernia repairs, bowel anastomoses, and solid organ removal [11,22,26,[32][33][34][35][36]. Additionally, the muscular stomach wall will easily tolerate the shearing forces associated with intra-abdominal endoscopic manipulation.…”
Section: Peritoneal Cavity Accessmentioning
confidence: 99%
“…With this technique it is assumed that less postoperative pain, faster recovery and reduced abdominal scarring can be achieved [1]. For this, organs such as the vagina [2][3][4], the colon [5] or the stomach [6,7] are penetrated.…”
Section: Introductionmentioning
confidence: 99%